LEVEL OF PERIPHERAL NEUROPATHY IN TYPE 2 DIABETES MELLITUS PATIENTS IN JEMBER DISTRICT - Ana Nistiandani; Jon Haffan Sutawardana; Risma Eka Putri Ariyani K.D (UPT Penerbitan Universitas Jember, 2022)
Diabetic neuropathy is a heterogeneous entity, consisting of peripheral sensorimotor and autonomic nerve dysfunction conditions. Diabetic peripheral neuropathy has a broad impact on patients, including recurrent infections, ulcers that do not heal and amputations of fingers and toes. This study aims to be able to overcome these risks, screening for neuropathy can be carried out including autonomic, sensory, and motor examinations.The research method uses a cross-sectional exploratory quantitative descriptive. The sample is 100 people using probability sampling method, namely multistage random sampling. The research locations are in 5 working areas of the Jember District Health Center (Bangsalsari, Umbulsari, Kalisat, Arjasa, and Patrang). Inclusion criteria for Type 2 Diabetes Mellitus (T2DM) patients aged 18 - 65 years, diagnosed with T2DM, did not have diabetic ulcers, did not have amputation of both legs, and suffered > 1 year. The exclusion criteria were no hospitalization and no communication disorders. The research instrument used the Michigan Diabetic Neuropathy Score (MDNS), Michigan Neuropthy Screening Instrument (MNSI), screening with the Ipswich Touch Test (IpTT), screening with the Monofilament Test.T2DM respondents experienced multiple autonomic damage to the right leg (52%; 53%). Sensory damage in T2DM patients on the right and left legs showed normal results (63%). Motor damage is dominated by normal conditions on the right and left legs as much as (49%; 52%) and there is a decrease in muscle strength on the right and left (50%; 47%).Based on the results, there is still a moderate risk of T2DM patients experiencing peripheral neuropathy. The provision of nursing care in screening early conditions is an action to reduce risk and improve the patient's quality of life.